Bimbingan Teknis Kinerja Pengawas Tempat Pemungutan Suara pada Pilkada 2020 di Era Pandemi Covid 19 - Ricky Santoso Muharam (Jurnal Surya Masyarakat, 2021)
Understanding of duty as a supervisor of polling places certainly needs to be given a thorough of various materials ranging from regulations on the selection of regional heads, regulations on the supervision of regional head elections during the Covid-19 pandemic, the code of ethics and the use of the election surveillance system (SIWASLU) need to be clearly understood.  This activity is carried out in two stages, namely technical guidance phase 1 and technical guidance phase 2 starting from the preparatory stage, material briefing, practice, posttest and questionnaire filling.  The results of this activity resulted in understanding for members of the polling station supervisor (PTPS) in carrying out their responsibilities   from regulatory understanding, supervision of health protocols as supervisors, code of ethics and commitment to contribute to becoming PTPS.   PTPS commitment to be able to contribute back to become a member of the TPS election supervisor for the 2024 elections correspondents answered 28 people (47.5%) willing to return to become PTPS in the   upcoming   elections or local elections, 28 people (47.5%) answer still in doubt or maybe willing to return to become PTPS and 3 people or about (5.1%) do not want to join the PTPS for the 2024 regional elections or presidential elections.